In-plane coherent control of plasmon resonances for plasmonic switching and encoding - Jiang, Liyong (2019)
Considerable attention has been paid recently to coherent control of plasmon resonances in metadevices for potential applications in all-optical light-with-light signal modulation and image processing. Previous reports based on out-of-plane coherent control of plasmon resonances were established by modulating the position of a metadevice in standing waves. Here we show that destructive and constructive absorption can be realized in metallic nano-antennas through in-plane coherent control of plasmon resonances, which is determined by the distribution rule of electrical-field components of nano-antennas. We provide proof-of-principle demonstrations of plasmonic switching effects in a gold nanodisk monomer and dimer, and propose a plasmonic encoding strategy in a gold nanodisk chain. In-plane coherent control of plasmon resonances may open a new avenue toward promising applications in optical spectral enhancement, imaging, nanolasing, and optical communication in nanocircuits.